Stratum corneum lipid liposome-encapsulated panomycocin: preparation, characterization, and the determination of antimycotic efficacy against Candida spp. isolated from patients with vulvovaginitis in an in vitro human vaginal epithelium tissue model - İzgü F (Dove Medical Press, 2017)
Fatih İzgü,1 Günce Bayram,2 Kübra Tosun,2 Demet İzgü3 1Department of Molecular Biology and Genetics, Middle East Technical University, Ankara, Turkey; 2Department of Biotechnology, Graduate School of Natural and Applied Sciences, Middle East Technical University, Ankara, Turkey; 3Biology Department, TED Ankara College, Ankara, Turkey Abstract: In this study, a liposomal lyophilized powder formulation of panomycocin was developed for therapeutic purposes against vulvovaginal candidiasis which affects 80% of women worldwide. Panomycocin is a potent antimycotic protein secreted by the yeast Wickerhamomyces anomalus NCYC 434. This study involved the preparation of panomycocin-loaded stratum corneum lipid liposomes (SCLLs), characterization of the SCLLs, and determination of antimycotic efficacy of the formulation against Candida albicans and Candida glabrata clinical vaginal isolates in a human vaginal epithelium tissue model. The encapsulation and loading efficiencies of SCLLs were 73% and 76.8%, respectively. In transmission electron microscopy images, the SCLLs appeared in the submicron size range. Dynamic light scattering analyses showed that the SCLLs had uniform size distribution. Zeta potential measurements revealed stable and positively charged SCLLs. In Fourier transform infrared spectroscopy analyses, no irreversible interactions between the encapsulated panomycocin and the SCLLs were detected. The SCLLs retained >98% of encapsulated panomycocin in aqueous solution up to 12 hours. The formulation was fungicidal at the same minimum fungicidal concentration values for non-formulated pure panomycocin when tested on an in vitro model of vaginal candidiasis. This is the first study in which SCLLs and a protein as an active ingredient have been utilized together in a formulation. The results obtained in this study led us to conduct further preclinical trials of this formulation for the development of an effective topical anti-candidal drug with improved safety. Keywords: antifungal protein, panomycocin, exo-β-1,3-glucanase, stratum corneum lipid liposome, vulvovaginitis, Candida spp.